Penerapan Pengaruh Metode Brainstorming Dalam Meningkatkan Kemampuan Berbicara Siswa Kelas VIII SMP Negeri 25 Makassar - Rahman, Arif Didi; Supriadi, Supriadi; Erniati, Erniati (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
This study aims to determine the application of the influence of the brainstorming method in improving the speaking ability of class VIII students of SMP Negeri 25 Makassar totaling 22 students. The population of this study was class VIII students. The sample in this study was class VIII students and class governance with a total of 22 students consisting of 13 women and 9 men. Sampling was carried out in a simple way, namely by dividing groups and selecting students randomly. This study was conducted in two cycles, namely cycle I and cycle II. Each cycle was carried out according to the changes to be achieved between cycle I and cycle II whose components were interrelated. Data collection was carried out through observation of students' speaking abilities, then analyzed quantitatively. The results of the study showed that learning using the brainstorming method in class VIII-B students of SMP Negeri 25 Makassar, in cycle I did not experience a significant increase, both in the results of the recapitulation of speaking abilities in cycle I and in the results of the recapitulation of the influence of using the brainstorming method. Speaking ability is categorized as lacking, as seen from the percentage of achievement of 53.33%. In cycle II, there was a significant increase, both in the results of the recapitulation of speaking ability and the results of the recapitulation of the influence of the brainstorming method with a percentage achievement of 62.22% which was categorized as sufficient.